The Relationship Between the Need to Belong and Nature Relatedness: The Moderating Role of Independent Self-Construal - Li, Liman Man Wai; Liu, Mengru; Ito, Kenichi (Frontiers in Psychology, 2021)
The perception of the relationship between humans and nature is important for promoting not only pro-environmental behaviors but also psychological well-being. The present research explored how people’s self-construal would moderate the relationship between the need to belong, the desire for social acceptance and connectedness and perceived nature relatedness. Two studies using community samples with diverse demographic characteristics in two different cultures (Study 1: the United States; Study 2: Singapore) obtained consistent findings. The results showed that independent self-construal, which emphasizes separateness from others in the social contexts, moderated the relationship between the need to belong and nature relatedness. Specifically, the need to belong was negatively associated with nature relatedness among people with a stronger independent self-construal, while this pattern was not significant among those with a weaker independent self-construal. No evidence for the moderating role of interdependent self-construal was found in the two studies. These findings highlighted the importance of non-nature experience in understanding people’s perception of human-nature relationships.